Physical Education Preservice Teachers' Academic and Social Engagement in Online Kinesiology Course. Issue 3 (3rd July 2019) - Sato, Takahiro; Haegele, Justin A.
Abstract: The purpose of this study was to investigate physical education preservice teachers' academic and social engagement in an online life-span motor development course. This study was based on theory of transactional distance. Seven undergraduate physical education majors, who were enrolled in an online course at a Midwestern public university in the United States, participated in this study. Data collection included face-to-face open-ended interviews, bulletin board discussion logs, and research writing projects. A constant comparative method was used to interpret the data. Four interrelated themes emerged from the pr-service teachers' narratives; transition from face-to-face to online course learning, socially acceptable and critical responses, lack of writing skills, and appreciation of instructors' midterm evaluation. As online kinesiology courses continue to grow, success and failure of online courses should be gauged through instructional content, students' grade-based outcomes, cognitive development, writing skills, course completion rates, and kinesiology course matriculation.